ANALISIS KUALITAS PELAYANAN PADA PUSAT PENGENDALIAN MUTU KEMENTERIAN KELAUTAN DAN PERIKANAN DALAM MENDUKUNG EKSPOR HASIL PERIKANAN - Anin, Anin; Islah, Khikmatul (Universitas Gajah Putih, 2023)
A service must be able to provide a sense of satisfaction to service users. The Quality and Safety Control Center also provides services, the service of HACCP certification and registration numbers. This study aims to analyze the services quality at The Quality and Safety Control Center. Goverment Regulation No. 24 of 2018 concerning bussiness licensing services to be integrated electronically so that the Quality and Safety Control Center implements onlinebased services that result in changes to the way, process and system of service. This research is a qualitative research that uses data collection such as observation, interviews and documentation. Based on the results of the study, system has used application-based services, namely the Honest application for HACCP certification services and Sisterkaroline for registration number services. With this application, it makes easier for stakeholders to apply for services. However, there are several things that need to be considered, such the internet network and servers which are important in supporting online system services. In addition, with the online single submission (OSS) system the implementation of Goverment Regulation No. 11 of 2020 concerning job creation, services must be fast and easy so that service providers must prepare competent human resources, supporting facilities and infrastructure. The results of the analysis that the researcher carried out, it concluded that the quality of service at the system was good but not optimal.